2021
DOI: 10.3390/biom11091382
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Target of Rapamycin Complex 1 Signaling Links Hypoxia to Increased IGFBP-1 Phosphorylation in Primary Human Decidualized Endometrial Stromal Cells

Abstract: Insulin-like growth factor-1 (IGF-1) bioavailability in pregnancy is governed by IGF binding protein (IGFBP-1) and its phosphorylation, which enhances the affinity of IGFBP-1 for the growth factor. The decidua is the predominant source of maternal IGFBP-1; however, the mechanisms regulating decidual IGFBP-1 secretion/phosphorylation are poorly understood. Using decidualized primary human endometrial stromal cells (HESCs) from first-trimester placenta, we tested the hypothesis that mTORC1 signaling mechanistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…To provide support for a functional interaction between decidual PKA and IGFBP-1, we performed IP of IGFBP-1 as in our recent study using primary decidualized HESC cultured in hypoxia or normoxia. 29 Using IP samples of decidualized primary HESC, we performed PRM-MS analysis to detect the presence and autophosphorylation status of PKA. PKA-specific peptides from the IGFBP-1 immunoprecipitates collected from cultured decidual HESC samples were successfully detected (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To provide support for a functional interaction between decidual PKA and IGFBP-1, we performed IP of IGFBP-1 as in our recent study using primary decidualized HESC cultured in hypoxia or normoxia. 29 Using IP samples of decidualized primary HESC, we performed PRM-MS analysis to detect the presence and autophosphorylation status of PKA. PKA-specific peptides from the IGFBP-1 immunoprecipitates collected from cultured decidual HESC samples were successfully detected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11 In addition, involvement of PKC together with CK2 was reported in decidualized primary HESC cultured under hypoxic conditions. 29 Decidual IGFBP-1 regulates the bioavailability of IGF-1 within the local environment of the placenta. 1 In the current study, we have not directly shown that PKA-mediated phosphorylation affects the affinity of IGFBP-1 to bind IGF-1 and hence IGF-1 bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations